Prevalence of Dyslipidemia in HIV-Positive Women with HPV Coinfection: A Preliminary Study - Mônika Machado de Carvalho; Karina Donato Fook; Maria José Abigail Mendes Araújo; Sulayne Janayna Araújo Guimarães; Camila Penha Abreu Souza; Carla Déa Trindade Barbosa; Ana Cléa Cutrim Diniz de Morais; Alessandra Costa de Sales Muniz; Deborah Rocha de Araújo; Maria Fernanda Bezerra Lima Bertolaccini; Ilka Kassandra Pereira Belfort; Marcelo de Souza Andrade; et al. (Scientifica)
Objective. The present study aimed to evaluate the lipid profile and atherogenic indexes in HIV-positive women with and without coinfection with human papillomavirus. Methods. Preliminary study was conducted with HIV-positive women. Laboratory tests (lipid profile, glycid profile, and atherogenic indexes) and detection of human papillomavirus (nested PCR technique using PGMY 09 and 11 primers, GP+5, and GP+6) were performed. For the analysis of the results, the data were categorized into two groups: with coinfection (HIV+/HPV+) and without coinfection (HIV+/HPV–). Results. Eighty-two HIV-positive women, aged between 35 and 49 years, participated in this study among whom 50% had HPV coinfection (HIV+/HPV+). Regarding comorbidities, there was a predominance of dyslipidemia (46.3%). The analysis of laboratory determinations and atherogenic indexes showed statistical relevance in the serum concentrations of total cholesterol (p=0.04), LDL cholesterol (p=0.03), and non-HDL cholesterol (p=0.04), as well as for the Castelli I index, Castelli II index, and atherogenic coefficient (p=0.04, 0.04, and 0.03, respectively). Conclusion. The present study demonstrated a correlation between the lipid profile and atherogenic indexes with HIV/HPV coinfection, demonstrating a possible synergy between these viruses. However, further studies in this area must be carried out.